2015
DOI: 10.1513/annalsats.201502-077bc
|View full text |Cite
|
Sign up to set email alerts
|

Open Lung Biopsy among Critically Ill, Mechanically Ventilated Patients: A Meta-Analysis

Abstract: Rationale: Open lung biopsy may be performed to guide therapy in mechanically ventilated patients with diagnostic uncertainty regarding etiology of pulmonary infiltrates. Current evidence for open lung biopsy in mechanically ventilated patients comes from single-center case series.Objectives: We performed a metaanalysis of case series to determine diagnoses, complications, and changes in therapy after lung biopsy in critically ill patients requiring mechanical ventilation. Methods:We searched Medline for case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 17 publications
(15 reference statements)
9
31
1
Order By: Relevance
“…Complication rate of the TBLB was low (11.9%) in the present study, although there was one serious adverse event with ultimately fatal outcome. In contrast, complications after SLB in mechanically ventilated patients occur in about 29%, which are mainly attributable to a high number of persistent air-leaks [2]. Pneumothorax incidence (12.5%) was comparable to previous studies [6][7] although one pneumothorax was related to transbronchial cryobiopsy, and there was no case of persistent air-leak.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Complication rate of the TBLB was low (11.9%) in the present study, although there was one serious adverse event with ultimately fatal outcome. In contrast, complications after SLB in mechanically ventilated patients occur in about 29%, which are mainly attributable to a high number of persistent air-leaks [2]. Pneumothorax incidence (12.5%) was comparable to previous studies [6][7] although one pneumothorax was related to transbronchial cryobiopsy, and there was no case of persistent air-leak.…”
Section: Discussionsupporting
confidence: 63%
“…In contrast, the histopathological result of a lung biopsy may provide important information on the underlying disease and could have signi cant impact on treatment decisions. Surgical lung biopsy (SLB) is the commonly used technique in such patients [2][3], but hypoxemia may worsen dramatically with single-lung ventilation, and the procedure usually requires a transfer from the intensive care unit (ICU) to the operating theater. Alternatively, bronchoscopic, transbronchial lung biopsy (TBLB, by means of forceps biopsy or cryobiopsy) is available, which also can be performed at the bedside in the ICU in the event of mechanical ventilation [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 37% (19/51) of the patients had a steroid-sensitive pathologic disease pattern (OP, acute interstitial pneumonia, acute exacerbation of usual interstitial pneumonia, eosinophilic pneumonia, pneumocystis pneumonia, alveolar hemorrhage and amiodarone toxicity); these patients had significantly better outcomes than patients with steroid-resistant pathologies (in-hospital mortality rate: 37% vs. 65%; 180-day mortality rate: 37% vs. 75%). In our study based on the combined data of reported cases, the summary diagnostic yield of TBLC was 92%, and 56% of patients had a diagnosis other than DAD, which led to management changes in 80% of patients (similar to SLB) (19). These results indicate that TBLC may be an alternative biopsy method to SLB for patients with nonresolving ARDS.…”
Section: Discussionmentioning
confidence: 60%
“…One of the most important advantages of this novel technique over SLB is the superior safety profile. The overall complication rate of SLB is about 30%, most of which (71%) are persistent air leaks (19); this rate of complications is significantly higher than that for TBLC (8%).…”
Section: Discussionmentioning
confidence: 86%
“…However, these assays require the ex vivo expansion of peripheral blood lymphocytes (PBLs) via stimulation and are not practical in clinical settings (25). In addition, lung tumor biopsy to examine intratumoral CTL infiltration is invasive (26). Therefore, it may be preferable to identify biomarkers from easily available human materials, including blood, using the predictive power that has been demonstrated to associate well with overall survival (OS) rate (27).…”
Section: Introductionmentioning
confidence: 99%